Accessibility to healthcare services in Poland at the initial stage of SARS-CoV-2 pandemic – patient perspective - Bartłomiej Chmielowiec; Melanie Raczek; Jarosław Chmielewski; Marta Puścion; Magdalena Florek-Łuszczki (Medycyna Ogólna i Nauki o Zdrowiu, 2022)
Introduction and objective The SARS-CoV-2 pandemic is a great challenge for the Polish healthcare system. This event had a significant impact on the availability of healthcare services and the exercising of patient rights due to the need to secure current requirements related to the pandemic. The aim of the article is presentation of the issue of availability of health services for Polish patients throughout the initial period of the SARS-CoV-2 pandemic.